2018
DOI: 10.1039/c8ra02058b
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of thermoelectric performance of PEDOT:PSS films by post-treatment with a superacid

Abstract: Treatment of PEDOT:PSS films with a superacid results in remarkable improvement of thermoelectric performance with a power factor of 142 μW m−1 K−2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
92
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 129 publications
(102 citation statements)
references
References 45 publications
10
92
0
Order By: Relevance
“…Moreover, the thermal properties of PEDOT:PSS films were investigated and the ρ, b, Cp, and κ of the pristine and BMIM-TFSI-SFS-F-PEDOT:PSS films are measured ( Table 3). The κ of the pristine PEDOT:PSS film was in accordance with those reported by independent groups (Lee et al, 2014a;Wang et al, 2015Wang et al, , 2018. The pulsed light heating thermoreflectance method was used to determine b at room temperature (Baba et al, 2011;Kyaw et al, 2018).…”
Section: Codesupporting
confidence: 65%
See 1 more Smart Citation
“…Moreover, the thermal properties of PEDOT:PSS films were investigated and the ρ, b, Cp, and κ of the pristine and BMIM-TFSI-SFS-F-PEDOT:PSS films are measured ( Table 3). The κ of the pristine PEDOT:PSS film was in accordance with those reported by independent groups (Lee et al, 2014a;Wang et al, 2015Wang et al, , 2018. The pulsed light heating thermoreflectance method was used to determine b at room temperature (Baba et al, 2011;Kyaw et al, 2018).…”
Section: Codesupporting
confidence: 65%
“…b (J/S 0.5 m 2 ) Cp (J/gK) ρm (g/cm 3 ) κ (W/m) attributable to the improvement of the number of ordered aggregates associated with interchain π-π stacking between the PEDOT chain and the enhancement of the crystallinity of the PEDOT:PSS film. Therefore, the XRD results displayed that compared to the pristine films, IL dedoped PEDOT:PSS films showed an enhanced interchain coupling of PEDOT:PSS with a more densely packed PEDOT and lamella stacking between two assemblies, resulting in an improved S of the films through interface scattering (Kim et al, 2014;Wang et al, 2018). Moreover, the thermal properties of PEDOT:PSS films were investigated and the ρ, b, Cp, and κ of the pristine and BMIM-TFSI-SFS-F-PEDOT:PSS films are measured ( Table 3).…”
Section: Codementioning
confidence: 99%
“…Studies showed that the s of PEDOT:PSS lms could be greatly enhanced with various post-treatment methods. [15][16][17][18][19][20][21][22][23] These post treatments enlarge the charge carrier concentration, and bipolaron are the main charge carriers. However, this high doping level results in a small S of PEDOT:PSS because of the extra charge carriers.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the π-conjugated polymers successfully employed are based on polyaniline, polypyrrole and poly(3,4-ethylenedioxythiophene) (PEDOT). Many studies have aimed to enhance the properties such as the electronic conductivity, by adding high boiling point solvents [ 9 ], superacids [ 10 ] or ionic liquids [ 11 ], mechanical properties [ 12 ] or employing hybrid architectures [ 13 ], even showing metallic conductivities of 6259 ± 1468 S cm −1 for thin post-treated films [ 14 ] and totally flexible foils [ 12 ]. These π-conjugated polymers can be either functionalized with polyelectrolytes and polymer electrolytes via pendant groups [ 15 ], or form copolymers and blends with other polymers (e.g., polyethylene oxide (PEO) [ 4 ] and polystyrene sulfonate (PSS) [ 12 ]), which provide the ionic conductivity.…”
Section: Introductionmentioning
confidence: 99%